Beyond identity and generations: bringing life course theory to studies of older gay men - Rosenfeld, Dana; Ramirez-Valles, Jesus (Frontiers in Sociology, 2024)
The last century’s numerous, rapid social changes affecting gay men make studies of gay male aging a ripe topic for life course theory, which views later life as the product of ‘the historic interplay among people's lives, structural contexts, and social change’ (O’Rand 1996: 230). That identifying as gay can occur at any point in the life course widens some life course theorists’ primary focus on early-life events to include those occurring throughout the life course. Yet most historically-attentive research on older gay men focuses on generations and identity development rather than on cohorts – groups who entered a system or context at the same time - or on the cumulative, concrete outcomes of encountering social change at a particular point in the life course. This article argues for gay male aging studies’ use of life course theory, specifically, its focus on cohort membership’s implications for later life, including cumulative disadvantage, in addition to more generationally-focused investigations. After briefly reviewing scholarship on older gay men, we introduce the life course approach and its critique by queer gerontologists for adopting a heteronormative view of the LGBT life course and eliding its distinctive contours. With particular attention to later-life concrete outcomes rather than identity formation, we explore key historical events in gay men’s lives that have produced (in the case of the AIDS epidemic) or could produce (for example, the Marriage Equality Act, the Don’t Ask, Don’t Tell policy) distinctive gay male cohorts. We then consider intra-cohort variation within gay male cohorts before exploring some the barriers to investigating cohorts and cohort effects among older gay men.